Nitrogen / fluorinated modified fumed silica composite powder as well as preparation method and application thereof

By introducing organic groups on the surface of the gas-phase silica and compounding it with quartz fibers, nitrogen/fluorinated modified gas-phase silica composite powder is prepared, which solves the problem of unstable dielectric properties of inorganic low-dielectric materials in extreme environments, and achieves the stable performance of high-fidelity communication cables under ultra-high temperature conditions.

CN119797883APending Publication Date: 2025-04-11DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411952219.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When existing inorganic low-dielectric materials are in service in extreme environments, their dielectric performance is unstable and cannot meet the performance requirements of high-fidelity communication cables under ultra-high temperature conditions.

Method used

By introducing organic groups on the surface of the vapor phase silica and compounding it with quartz fibers, nitrogen/fluorinated modified vapor phase silica composite powder is prepared, and the structure is further optimized by heat treatment method to reduce dielectric loss.

Benefits of technology

It achieves stable dielectric performance of high-fidelity communication cables under ultra-high temperature conditions, reduces dielectric loss and cable attenuation, and is suitable for aerospace and military communication fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797883A_ABST
    Figure CN119797883A_ABST
Patent Text Reader

Abstract

The invention relates to nitrogen / fluorinated modified fumed silica composite powder as well as a preparation method and application thereof, and solves the technical problems that a high-fidelity communication cable is unstable in performance and relatively large in attenuation under an ultrahigh-temperature condition. The prepared high-temperature-resistant high-fidelity communication cable internal insulation dielectric layer material can be applied to the fields of aerospace, military communication and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of modified materials, and in particular relates to a nitrogen / fluoride modified fumed silicon dioxide composite powder, a preparation method and an application thereof. Background Art

[0002] With the continuous development of fields such as aerospace, deep-sea exploration, and military communications, the demand for composite materials with low dielectric loss constant, low dielectric loss, and good operating stability in microelectronic devices and high-frequency communications for extreme environments is also increasing to ensure the stability of communication signals during transmission. Although organic low-dielectric materials have advantages such as low dielectric constant and easy processing, their dielectric properties are easily degraded when used in extreme environments such as ultra-high temperature, low temperature, and sudden temperature changes, and they cannot work effectively for a long time. Compared with organic low-dielectric materials, inorganic low-dielectric materials based on silica can maintain stable performance in extreme environments. However, due to their relatively high dielectric constant, traditional inorganic materials cannot meet the requirements for stable dielectric properties in extreme environments. Therefore, composite optimization and structural adjustment and upgrading of traditional inorganic materials have become urgent issues.

[0003] Although some research teams have used silica as the insulating dielectric material for communication cables, the dielectric loss is not sufficiently low due to the incomplete bonding of silica with quartz fiber, preventing the cable from achieving extremely low attenuation during fabrication and operation. Furthermore, the insulating dielectric layers of current mainstream high-temperature cables are mostly inorganic / organic composite materials, which are prone to failure in extreme environments, leading to cable breakdown. Their high-temperature resistance and dielectric properties need to be further improved. Therefore, developing a simple and rapid preparation method to construct a fumed silica composite quartz fiber structure and further reduce the dielectric loss of the cable insulation layer remains a significant challenge. Summary of the Invention

[0004] In response to the shortcomings of the prior art, the present invention aims to provide a nitrogen / fluoride-modified fumed silica composite powder, its preparation method, and applications. Specifically, it relates to a low-dielectric-loss nitrogen / fluoride-modified fumed silica composite powder for communication cables, its preparation, and applications. This invention overcomes the technical challenges of unstable performance and significant attenuation in high-fidelity communication cables under ultra-high temperature conditions. The resulting high-temperature-resistant, high-fidelity communication cable internal insulation dielectric material can be applied in aerospace, military communications, and other fields.

[0005] The invention provides a modified fumed silica composite material, which comprises quartz fiber and nitrogen / fluorinated modified fumed silica.

[0006] Preferably, the mass ratio of the quartz fiber to the nitrogen / fluorinated modified fumed silica is 1:40 to 1:0.1.

[0007] Preferably, the mass percentage of quartz fiber in the composite material is 5-80%, and further preferably, the mass percentage of quartz fiber in the composite material is 10-28%.

[0008] Nitrogen / fluoride modified fumed silica is nitrided or fluorinated fumed silica.

[0009] Preferably, the method for preparing the nitrogen / fluoride modified fumed silica comprises: modifying the fumed silica with a modifier under alkaline conditions to obtain the nitrogen / fluoride modified fumed silica.

[0010] The solvent used in the preparation of the nitrogen / fluorinated modified fumed silica is one or both of water and ethanol.

[0011] Furthermore, the preparation method of the nitrogen / fluoride modified fumed silica includes: mixing fumed silica, an alkaline catalyst, and a solvent to obtain a mixed liquid, then adding a modifier for modification, then centrifuging, washing, drying, and vacuum drying to obtain nitrogen / fluoride modified fumed silica; further, the concentration of fumed silica in the mixed liquid is 1 to 100 g / L, the concentration of the alkaline catalyst is 0.01 to 2 mol / L, and the solvent is deionized water and ethanol; wherein the volume ratio of deionized water to ethanol is 1:20 to 1:0.5.

[0012] Preferably, the modifier includes one or more of triethoxyfluorosilane, hexamethyldisilazane, hexamethylcyclotrisilazane, 1H,1H,2H,2H-perfluorodecyltrimethoxysilane, trimethoxy(1H,1H,2H,2H-nonafluorohexyl)silane, tridecafluorooctyltriethoxysilane, octamethylcyclotetrasilazane, and trimethylfluorosilane; the alkaline conditions are alkaline catalyst conditions, wherein the alkaline catalyst includes one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia water.

[0013] Preferably, the mass ratio of the fumed silica to the modifier is 1:10 to 1:0.1;

[0014] Preferably, the modification conditions are: temperature of 20 to 180° C., time of 0.25 to 36 h, and rotation speed of 100 to 1500 r / min.

[0015] Further preferably, the modification conditions are: temperature of 40 to 100° C. and time of 8 to 24 hours.

[0016] Preferably, the quartz fiber is a quartz fiber that has been ball-milled;

[0017] Preferably, the quartz fiber after ball milling: the quartz fiber is ball milled, wherein the mass ratio of the ball milling beads to the quartz fiber is 10:1 to 30:1, the ball milling speed of the quartz fiber is 100 to 600 r / min, and the ball milling time is 2 to 50 min.

[0018] Preferably, the mass ratio of the quartz fiber to the nitrogen / fluorinated modified fumed silica is 1:40 to 1:0.1.

[0019] The invention provides a preparation method of a modified fumed silica composite material, comprising: mixing quartz fiber and nitrogen / fluorinated modified fumed silica and then performing heat treatment.

[0020] Preferably, the heat treatment temperature is 50-900°C and the time is 0.5-20h;

[0021] More preferably, the heat treatment temperature is 300-900° C., and the time is 1-16 hours.

[0022] Furthermore, drying is performed before the heat treatment: the drying temperature is 75-85° C., and the drying time is 12-48 hours; the drying temperature after grinding is 75-85° C., and the drying time is 2-12 hours.

[0023] Furthermore, the heat treatment is followed by grinding.

[0024] The present invention provides a communication cable, which comprises an insulating dielectric layer; wherein the insulating dielectric layer material is the modified fumed silica composite material.

[0025] The present invention provides an application of the modified fumed silica composite material or the communication cable in the fields of aerospace and military communications.

[0026] The present invention utilizes nitrogen / fluoride-modified fumed silica and compounds it with quartz fiber to produce a low-dielectric-loss nitrogen / fluoride-modified fumed silica composite powder. Organic groups are introduced onto the surface of the fumed silica, compounded with the quartz fiber, and then heat-treated to produce the low-dielectric-loss nitrogen / fluoride-modified fumed silica composite powder, which serves as the internal insulating dielectric layer material for high-fidelity communication cables.

[0027] Beneficial effects

[0028] The nitrogen / fluorinated modified fumed silica composite powder of the present invention has a low dielectric loss constant and is resistant to ultrahigh temperatures, and can effectively solve the problem of performance failure of high-fidelity communication cables under ultrahigh temperature conditions.

[0029] The preparation process of the nitrogen / fluorination modified fumed silicon dioxide composite powder of the present invention is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The dielectric constant of the low dielectric loss nitrogen / fluoride modified fumed silica composite powder obtained in Examples 1, 2, 3, and 4;

[0031] Figure 2 The dielectric loss of the low dielectric loss nitrogen / fluoride modified fumed silica composite powder obtained in Examples 1, 2, 3, and 4;

[0032] Figure 3 This is a scanning electron microscope image (5000 times) of the silicon dioxide low dielectric loss composite powder obtained in Example 1;

[0033] Figure 4 This is a scanning electron microscope image (5000 times) of the silicon dioxide low dielectric loss composite powder obtained in Example 2;

[0034] Figure 5 This is a scanning electron microscope image (10,000 times) of the silicon dioxide low dielectric loss composite powder obtained in Example 3;

[0035] Figure 6 This is a scanning electron microscope image (10,000 times) of the silicon dioxide low dielectric loss composite powder obtained in Example 4;

[0036] Figure 7 This is the thermogravimetric graph of the silicon dioxide low dielectric loss composite powder obtained in Example 4;

[0037] Figure 8 This is a structural diagram of a radio frequency coaxial communication cable. Fumed silica composite powder is mainly used in the insulating dielectric layer. DETAILED DESCRIPTION

[0038] Below in conjunction with specific embodiment, further set forth the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used in limiting the scope of the present invention.In addition, should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope limited by the appended claims of the application.

[0039] Example 1

[0040] 1. Preparation of Nitrogen / Fluoride Modified Fumed Silica

[0041] (1) Add 20 g of fumed silica, 10 g of ammonia water, 20 g of deionized water, and 100 g of ethanol to a beaker. Stir evenly with a glass rod, then add a magnetic stirrer. Set the magnetic stirrer speed to 800 rpm and pre-stir at 100°C for 1 h.

[0042] (2) Add 5 g of hexamethyldisilazane to the stirred mixture, place in an oil bath with a speed of 400 r / min and a temperature of 60°C, and stir for 2 h;

[0043] (3) After the reaction is completed, the reaction is transferred to a centrifuge, the centrifuge parameters are set to 6000 r / min, the centrifugation time is 4 min, and the precipitate is obtained by centrifugation washing;

[0044] (4) Transfer the precipitate into a beaker and dry it in an electric forced air oven at 100°C for 24 h;

[0045] (5) The dried product was transferred to a vacuum oven and dried at 80°C for 12 h to obtain nitrogen / fluoride modified fumed silica.

[0046] 2. Preparation of Quartz Short Fibers

[0047] The ball mill speed was set to 200 r / min, the ball milling time was 6 min, 6 g of quartz fiber with a diameter of 5 to 9 μm and 60 g of ball milling beads were placed in a ball milling jar and ball milled to obtain uniform quartz short fibers.

[0048] 3. Preparation of low dielectric loss nitrogen / fluoride modified fumed silica composite powder

[0049] (1) Add 4 g of quartz short fiber and 16 g of nitrogen / fluorinated modified fumed silica powder to a beaker and stir evenly;

[0050] (2) The sample was placed in an electric heated air drying oven at 80°C and dried for 24 h;

[0051] (3) The sample was transferred to a mortar and ground evenly, and then placed in an electric heated blast oven at 80°C for secondary drying for 2 h;

[0052] (4) The sample was transferred into a crucible and placed in a muffle furnace for heat treatment at 400 °C for 5 h;

[0053] (5) The sample was transferred into a mortar and ground evenly to obtain a low dielectric loss nitrogen / fluoride modified fumed silica composite powder.

[0054] Example 1 The dielectric constant and dielectric loss of the sample were tested using a broadband dielectric impedance spectrometer at an air humidity of 30%. The test results are as follows: Figure 1 As shown in Table 1, the dielectric constant is 2.22 at 20MHz and the dielectric loss reaches 0.029. The cable properties are shown in Table 1, and the SEM photos of the composite powder are shown in Table 1. Figure 3As shown, it can be seen that the composite of quartz fiber and fumed silica is not sufficient compared to Example 4, and the dielectric loss of the composite powder is larger than that of Example 4. This may be because the nitrogen / fluorination modification time is too short, and the organic groups are not completely grafted to the fumed silica surface, which affects the composite effect and thus the dielectric properties of the powder and the cable attenuation. Therefore, the nitrogen / fluorination modification time should be increased to allow the organic groups to fully graft to the fumed silica surface to reduce the dielectric loss of the composite powder and the cable attenuation.

[0055] Example 2

[0056] 1. Preparation of Nitrogen / Fluoride Modified Fumed Silica

[0057] (1) Add 50 g of fumed silica, 20 g of sodium hydroxide, 50 g of deionized water, and 600 g of ethanol to a beaker. Stir evenly with a glass rod, then add a magnetic stirrer. Set the magnetic stirrer speed to 900 rpm and pre-stir at 40°C for 6 h.

[0058] (2) Add 30 g of tridecafluorooctyl triethoxysilane to the stirred mixture, place in an oil bath with a speed of 1000 r / min and a temperature of 80°C, and stir for 12 h;

[0059] (3) After the reaction is completed, the reaction is transferred to a centrifuge, the centrifuge parameters are set to 6800 r / min, the centrifugation time is 8 min, and the precipitate is obtained by centrifugal washing;

[0060] (4) The precipitate was transferred to a beaker and dried in an electric forced air oven at 80°C for 36 h;

[0061] (5) The dried product was transferred to a vacuum oven at 80°C and dried for 20 h;

[0062] (6) The dried product was transferred into a mortar and ground evenly to obtain nitrogen / fluoride modified fumed silica.

[0063] 2. Preparation of Quartz Short Fibers

[0064] The ball mill speed was set to 250 r / min, the ball milling time was 12 min, 9 g of quartz fiber with a diameter of 5 to 9 μm and 120 g of ball milling beads were placed in a ball milling jar and ball milled to obtain uniform quartz short fibers.

[0065] 3. Preparation of low dielectric loss nitrogen / fluoride modified fumed silica composite powder

[0066] (1) Add 6 g of quartz short fiber and 20 g of nitrogen / fluorinated modified fumed silica powder into a beaker and stir evenly;

[0067] (2) The sample was transferred to an electric heated forced air oven at 80°C and dried for 36 h;

[0068] (3) The sample was transferred to a mortar and ground evenly, and then placed in an electric heated blast oven at 80°C for secondary drying for 2 h;

[0069] (4) The sample was transferred into a crucible and placed in a muffle furnace for heat treatment at 250°C for 4 h. After the heat treatment, the surface powder was removed;

[0070] (5) The sample was transferred into a mortar and ground evenly to obtain a low dielectric loss nitrogen / fluoride modified fumed silica composite powder.

[0071] Example 2 The dielectric constant and dielectric loss of the sample were tested using a broadband dielectric impedance spectrometer at an air humidity of 30%. The test results are as follows: Figure 1 As shown in Table 1, the dielectric constant is 2.65 at 20MHz and the dielectric loss reaches 0.012. The cable performance is shown in Table 1, and the SEM photo of the composite powder is shown in Table 1. Figure 4 As shown, it can be seen that the quartz short fibers and fumed silica are fully composited. The high dielectric constant of the composite powder is due to the excessive organic groups on its surface, which reduces the porosity and causes its dielectric constant to rise to 2.65. The cable attenuation is too large compared to Example 4 because the excessive organic groups on the surface of the composite powder during the cable preparation process lead to excessive cable density, which affects the cable performance and increases the cable attenuation to 4.34dB / m. Therefore, the heat treatment temperature of the composite powder should be further increased to remove the organic groups while ensuring the composite effect, thereby reducing the powder dielectric constant and cable density, thereby reducing cable attenuation.

[0072] Example 3

[0073] 1. Preparation of Nitrogen / Fluoride Modified Fumed Silica

[0074] (1) Add 30 g of fumed silica, 12 g of potassium hydroxide, 15 g of deionized water, and 200 g of ethanol to a beaker. Stir with a glass rod for 7 min, then add a magnetic stirrer. Set the magnetic stirrer speed to 600 rpm and pre-stir at 60°C for 3 h.

[0075] (2) Add 4 g of 1H,1H,2H,2H-perfluorodecyltrimethoxysilane to the stirred mixture, place in an oil bath with a speed of 700 r / min and a temperature of 75°C, and stir for 16 h;

[0076] (3) After the reaction is completed, the reaction is transferred to a centrifuge, the centrifuge parameters are set to 7800 r / min, the centrifugation time is 7 min, and the precipitate is obtained by centrifugal washing;

[0077] (4) Transfer the precipitate into a beaker and dry it in an electric forced air oven at 80°C for 24 h;

[0078] (5) The dried product was transferred to a vacuum oven at 80°C and dried for 12 h;

[0079] (6) The dried product was transferred into a mortar and ground evenly to obtain nitrogen / fluoride modified fumed silica.

[0080] 2. Preparation of Quartz Short Fibers

[0081] The ball mill speed was set to 360 r / min, the ball milling time was 8 min, 8 g of quartz fiber with a diameter of 5 to 9 μm and 160 g of ball milling beads were placed in a ball milling jar and ball milled to obtain uniform quartz short fibers.

[0082] 3. Preparation of low dielectric loss nitrogen / fluoride modified fumed silica composite powder

[0083] (1) Add 6 g of quartz short fiber and 14 g of nitrogen / fluorinated modified fumed silica powder to a beaker, and then stir the sample evenly;

[0084] (2) The sample was placed in an electric heated air drying oven at 80°C and dried for 30 h;

[0085] (3) The sample was transferred to a mortar and ground evenly, and then placed in an electric heated blast oven at 80°C for secondary drying for 4 h;

[0086] (4) The sample was transferred into a crucible and placed in a muffle furnace for heat treatment at 560°C for 6 h. After the heat treatment, the surface powder was removed;

[0087] (5) The sample was transferred into a mortar and ground evenly to obtain a low dielectric loss nitrogen / fluoride modified fumed silica composite powder.

[0088] Example 3 The dielectric constant and dielectric loss of the sample were tested using a broadband dielectric impedance spectrometer at an air humidity of 30%. The test results are as follows: Figure 1 As shown in Table 1, the dielectric constant is 2.43 at 20MHz and the dielectric loss reaches 0.011. The cable performance is shown in Table 1, and the SEM photo of the composite powder is shown in Table 1. Figure 5 As shown, it can be seen that the quartz fiber and fumed silica are relatively fully composited, the dielectric loss of the composite powder is reduced to 0.011, and the cable attenuation is reduced to 1.21 dB / m. However, the impedance is too low compared to Example 4, falling below 48Ω. This may be because the quartz short fiber accounts for 30%, which is a high proportion. Therefore, the content of quartz short fiber should be reduced to improve the cable impedance.

[0089] Example 4

[0090] 1. Preparation of Nitrogen / Fluoride Modified Fumed Silica

[0091] (1) Add 24 g of fumed silica, 12 g of ammonia water, 24 g of deionized water, and 400 g of ethanol to a beaker. Stir with a glass rod for 10 min, then add a magnetic stirrer. Set the magnetic stirrer speed to 600 rpm and pre-stir at 80°C for 1 h.

[0092] (2) Add 14 g of 1H,1H,2H,2H-perfluorodecyltrimethoxysilane to the stirred mixture, place in an oil bath with a speed of 1000 r / min and a temperature of 80°C, and stir for 18 h;

[0093] (3) After the reaction is completed, the reaction is transferred to a centrifuge, the centrifuge parameters are set to 8000 r / min, the centrifugation time is 8 min, and the precipitate is obtained by centrifugal washing;

[0094] (4) Transfer the precipitate into a beaker and dry it in an electric forced air oven at 80°C for 24 h;

[0095] (5) The dried product was transferred to a vacuum oven at 80°C and dried for 12 h;

[0096] (6) The dried product was transferred into a mortar and ground evenly to obtain nitrogen / fluoride modified fumed silica.

[0097] 2. Preparation of Quartz Short Fibers

[0098] The ball mill speed was set to 360 r / min, the ball milling time was 12 min, 8 g of quartz fiber with a diameter of 5 to 9 μm and 160 g of ball milling beads were placed in a ball milling jar and ball milled to obtain uniform quartz short fibers.

[0099] 3. Preparation of low dielectric loss nitrogen / fluoride modified fumed silica composite powder

[0100] (1) Add 5 g of quartz short fiber and 20 g of nitrogen / fluoride modified fumed silica powder to a beaker, and then stir the sample evenly;

[0101] (2) The sample was transferred to an electric heated forced air oven at 80°C and dried for 32 h;

[0102] (3) The sample was transferred to a mortar and ground evenly, and then placed in an electric heated blast oven at 80°C for secondary drying for 4 h;

[0103] (4) The sample was transferred into a crucible and placed in a muffle furnace for heat treatment at 560°C for 6 h. After the heat treatment, the surface powder was removed;

[0104] (5) The sample was transferred into a mortar and ground evenly to obtain a low dielectric loss nitrogen / fluoride modified fumed silica composite powder.

[0105] Example 4 The dielectric constant and dielectric loss of the sample were tested using a broadband dielectric impedance spectrometer at an air humidity of 30%. The test results are as follows: Figure 1 As shown in Table 1, the dielectric constant is 2.03 and the dielectric loss is 0.010 at 20MHz. The cable performance is shown in Table 1, and the thermal weight loss diagram is shown in Figure 7 As shown in the figure, the mass loss of the composite powder is less than 1% in the range of 800℃, which verifies the high temperature resistance of the composite powder. The SEM photo of the composite powder is shown in Figure 6 As shown in the figure, it can be seen that due to sufficient surface modification time, sufficient organic groups were grafted onto the fumed silica surface, reducing the surface energy and allowing for sufficient composite between the quartz fiber and the fumed silica. Simultaneously, increasing the heat treatment temperature of the composite powder while maintaining the composite effect also removed the organic groups within the composite powder, lowering the powder dielectric constant to 2.03. This reduced the dielectric loss of the composite powder to 0.010 and the cable attenuation to 0.75dB / m. The appropriate ratio of fumed silica to quartz fiber ensured a cable impedance match of 50±2Ω.

[0106] The present invention will eventually be applied to the insulating dielectric layer of high temperature resistant communication semi-steel coaxial cables, the cable structure is as follows Figure 6 The cable consists of a stainless steel sheath, a copper outer conductor, an insulating layer and a copper inner conductor from the outside to the inside.

[0107] Table 1 shows the cable performance obtained by applying the low dielectric loss nitrogen / fluorinated modified fumed silica composite powder obtained in Examples 1, 2, 3, and 4 to the cable dielectric layer. After the cables were packaged with connectors, the cable samples were assembled and tested using a vector analyzer.

[0108] Table 1. Cable performance table

[0109]

Claims

1. A modified fumed silica composite material, characterized in that: The composite material comprises quartz fiber and nitrogen / fluorinated modified fumed silica.

2. The modified fumed silica composite material according to claim 1, characterized in that: The mass ratio of the quartz fiber to the nitrogen / fluorinated modified fumed silica is 1:40 to 1:0.

1.

3. The modified fumed silica composite material according to claim 1, characterized in that: The preparation method of the nitrogen / fluoride modified fumed silica comprises: modifying the fumed silica with a modifier under alkaline conditions to obtain the nitrogen / fluoride modified fumed silica; The quartz fiber is a quartz fiber that has been ball-milled.

4. The modified fumed silica composite material according to claim 3, characterized in that: The modifier includes one or more of triethoxyfluorosilane, hexamethyldisilazane, hexamethylcyclotrisilazane, 1H,1H,2H,2H-perfluorodecyltrimethoxysilane, trimethoxy(1H,1H,2H,2H-nonafluorohexyl)silane, tridecafluorooctyltriethoxysilane, octamethylcyclotetrasilazane, and trimethylfluorosilane; the alkaline conditions are alkaline catalyst conditions, wherein the alkaline catalyst includes one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia water.

5. The modified fumed silica composite material according to claim 3, characterized in that: The mass ratio of the fumed silica to the modifier is 1:10 to 1:0.1; The solvent used in the preparation of the nitrogen / fluorinated modified fumed silica is one or two of water and ethanol; The modification conditions are as follows: temperature of 20 to 180° C., time of 0.25 to 36 hours, and rotation speed of 100 to 1500 r / min.

6. The modified fumed silica composite material according to claim 3, characterized in that: The quartz fiber after ball milling: the quartz fiber is ball milled, wherein the mass ratio of the ball milling beads to the quartz fiber is 10:1 to 30:1, the ball milling speed of the quartz fiber is 100 to 600 r / min, and the ball milling time is 2 to 50 minutes.

7. A method for preparing a modified fumed silica composite material, comprising: The quartz fiber and the nitrogen / fluorinated modified fumed silica are mixed and then heat treated.

8. The preparation method according to claim 7, characterized in that: The heat treatment temperature is 50-900°C and the time is 0.5-20h; drying is performed before the heat treatment; The heat treatment is followed by a grinding treatment.

9. A communication cable, characterized in that: The communication cable comprises an insulating dielectric layer; wherein the insulating dielectric layer material is the modified fumed silica composite material as claimed in claim 1.

10. Use of the modified fumed silica composite material according to claim 1 or the communication cable according to claim 10 in the fields of aerospace and military communications.